Comportamento intra-específico do cupim Heterotermes tenuis (Hagen) (Isoptera, Rhinotermitidae) em condições de laboratório - Camargo-Dietrich, Célia Regina Rodrigues de [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Sociedade Brasileira de Zoologia, 2000)
Groups of Heterotemies tenuis (Hagen, 1858) from five infestation points were paired in bioassays to investigate the intercolony aggression. The combinations of arena sizes (Petri dishes of 6.0 and 9.0 cm) and temperatures (25 and 28 ºC) were assessed for effects on intraspecific agonism. Agonistic behavior was scored positive in arena if more than half of the starting number of termites was dead and injured after 17 hours. After the intraspecific encounters it was possible to delimitate three colonies from the five infestation points. No significant differential survival was seen in two different arena sizes and two different temperatures. These assays indicate that the factors governing the agonistic behavior in H. tenuis are complex and seems to be dependent on environmental conditions and individual characteristies (age, size and caste).
Intraspecific behavior of the termite Heterotermes tenuis (Hagen) (Isoptera, Rhinotermitidae) in laboratory conditions
Keywords: Isoptera; Rhinotermitidae; Heterotermes tenuis; intraspecific behavior